Association of serum pregnancy associated plasma protein: a with gestational diabetes mellitus - Begum, Khadiza; Saha, Mousumi; Tamanna, Jesika Rizvi; Ara Banu, Ferdous; Ferdous, Sharmin; Rahman, A. K. M. Mizanur; Akhtar, Nahreen (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Gestational diabetes mellitus is defined as diabetes diagnosed during pregnancy that is not clearly overt diabetes. GDM has many adverse consequences on the health of mother and fetus. Methods: This cohort study was carried out involving 77 women of 11 to14-week pregnant attending in the Gynecology & Obstetrics and Fetomaternal Medicine OPD, BSMMU from September 2020 to August 2021. Results: Respondents were divided into two groups. Low PAPP-A group (<0.5MoM) and normal PAPP-A group (>0.5MoM). In low PAPP-A group, out of 16 respondents, 8 (42.1%) developed GDM and remaining 8(13.8%) were euglycemic. Whereas, in normal PAPP-A group, out of 61 respondents, majority 50 (86.2%) were euglycemic and only 11 (57.9%) women developed GDM. A total 19 (24.68%) respondents developed GDM from both low and normal PAPP-A group. ROC analysis of PAPP-A level for detection of GDM, a AUC value of 0.889 (95% CI 0.818-0.960) found which was statistically significant. A cut off value of ≤16.80 showed the highest Youden index (0.652) with 89.4% sensitivity and 81% specificity, the accuracy was 83.35. Moreover, a cut off value ≤16.80 showed PPV and NPV of 62.1% and 95.9%, respectively. PAPP-A level of GDM detected (10.32±5.56) µg/ml was significantly lower from non GDM mothers (25.08 ±9.85) µg/ml, where p<0. 001. Conclusions: Study finding revealed that maternal serum PAPP-A level was lower in 11-14 weeks of pregnancy who subsequently developed GDM. So, a low PAPP-A level (<0.5 MoM) in 11-14 weeks of pregnancy is associated for development of GDM.